Asymmetric Information, Earnings Management and Cost of Equity - Dian Urna Fasihat; Rizkiana Iskandar; Lilis Marlina (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this study was to determine whether there is an influence of asymmetric information and earnings management on cost of equity. The total samples on this research are 241 that are determined using the purposive sampling method at manufacturing companies listed on the Indonesia stock exchange in 2015 to 2017. The analysis used is panel data regression. The findings indicate that asymmetric information affected the cost of equity, whereas earnings management had no effect on the cost of equity. The lack of impact from earnings management is due to the bias in investor perspectives on financial statements, where they believe the reported numbers are genuine and unaltered, without verifying whether a company employs earnings management practices or not.